ÉPOCA E REGULADOR VEGETAL NA PROPAGAÇÃO DE BARU POR ESTAQUIA - GONÇALVES, Nayara Feitosa; SOUZA, Mariana Conceição; SILVA, Mariele Trindade; SILVA, Adriana de Castro Correia da (ANAIS DO ENIC, 2017)
-